2013
DOI: 10.7567/jjap.52.01ac08
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hydrogen Dilution on ZnO Thin Films Fabricated via Nitrogen-Mediated Crystallization

Abstract: Hydrogenated ZnO thin films have been successfully deposited on glass substrates via a nitrogen mediated crystallization (NMC) method utilizing RF sputtering. Here we aim to study the crystallinity and electrical properties of hydrogenated NMC-ZnO films in correlation with substrate temperature and H2 flow rate. XRD measurements reveal that all the deposited films exhibit strongly preferred (001) orientation. The integral breadth of the (002) peak from the hydrogenated NMC-ZnO films is smaller than that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…b, two peaks spaced by 180° were observed for both ZnO and sapphire, since the crystal lattices of m‐plane ZnO and m‐plane sapphire are both rectangular with two‐fold symmetry. The c ‐axes of ZnO and that of sapphire perpendicularly crossed each other on the sapphire substrate, namely ZnO [0001] || sapphire and ZnO || sapphire [0001]. In this φ scan measurement, the ZnO (10–11) and sapphire (11–20) planes were used as the monitoring planes, where Bragg conditions were set to be satisfied.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…b, two peaks spaced by 180° were observed for both ZnO and sapphire, since the crystal lattices of m‐plane ZnO and m‐plane sapphire are both rectangular with two‐fold symmetry. The c ‐axes of ZnO and that of sapphire perpendicularly crossed each other on the sapphire substrate, namely ZnO [0001] || sapphire and ZnO || sapphire [0001]. In this φ scan measurement, the ZnO (10–11) and sapphire (11–20) planes were used as the monitoring planes, where Bragg conditions were set to be satisfied.…”
Section: Resultsmentioning
confidence: 99%
“…and , it was shown that the thickness and crystallographic properties were homogeneous across the substrate, and that the ZnO film was epitaxially grown on the sapphire substrate . In the direction lateral to the sapphire substrate, four small rectangular ZnO lattices are formed on one large sapphire rectangular lattice in the sapphire [0001] direction, indicating domain‐matching epitaxy , where the lattice mismatch in the ZnO [0001] direction is 9.7%, and that in the ZnO direction is 0.1%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the major drawback of adding H 2 is increased etching and reduction of the ZnO films during plasma treatment. More detailed informations about the influence of H 2 addition is given in the literature [86].…”
Section: Magnetron Sputteringmentioning
confidence: 99%